THU0312 Fibromyalgia Frequency in Patients with Acne Vulgaris. (9th June 2015) - Yazmalar, L.; Çelepkolu, T.; Batmaz, I.; Sarıyıldız, M.A.; Sula, B.; An, I.; Burkan, Y.K.; Alpaycı, M.; Uçak, H.; Çevik, R.
Abstract : Background: Acne vulgaris is a widespread inflammatory disease of skin. Among the general population, acne occurs in about 80% of teenagers and 25% of adults. 1 Many factors such as stress, genetic predisposition, bacterial infections, hormonal disorders, cosmetics, sun exposure, smoking or diet can cause acne. 2 According to our knowledge, by this time, fibromyalgia syndrome-related clinical symptoms such as fatigue, sleep disorders or anxiety have been addressed in patients with acne vulgaris. 3, 4 But, fibromyalgia syndrome has not been addressed. Objectives: The aim of the study was to evaluate the frequency of fibromyalgia syndrome and specify fibromyalgia syndrome-associated clinical symptoms in patients with acne vulgaris. Methods: Eighty-eight (60 females, 28 males) patients with acne vulgaris were enrolled in this study. In addition, 76 age and gender-matched healthy controls (62 females, 14 males) were included in the study. Acne vulgaris was evaluated using Global Acne Scale. Diagnosis of fibromyalgia syndrome was determined using The American College of Rheumatology 1990 criteria for the classification of fibromyalgia. Hospital Anxiety and Depression Scale was used for evaluation of anxiety. Results: There was no significant difference in age, gender or body mass index between two groups. The fibromyalgia syndrome frequency, sleep disturbance, anxiety, menstrual cycle disturbance and mean tender point counts were significantly greater among the acne patients relative to the controls. Although widespread body pain, fatigue, arthralgia, irritable bowel syndrome were more common among the acne patients, there were no significant differences between the acne patients and controls. Conclusions: The results of our study showed that fibromyalgia syndrome frequency is greater among acne vulgaris patients in comparison to control subjects. References: Chiu A, Chon SY, Kimball AB. The response of skin disease to stress: changes in the severity of acne vulgaris as affected by examination stres. Arch Dermatol. 2003 Jul;139(7):897-900. Albuquerque RG, Rocha MA, Bagatin E, Tufik S, Andersen ML. Could adult female acne be associated with modern life? Arch Dermatol Res. 2014 Oct;306(8):683-8. Misery L, Wolkenstein P, Amici JM, Maghia R, Brenaut E, Cazeau C, Voisard JJ, Taïeb C. Consequences of Acne on Stress, Fatigue, Sleep Disorders and Sexual Activity: A Population-based Study. Acta Derm Venereol. 2014 Nov 4. doi: 10.2340/00015555-1998. Silverberg JI, Silverberg NB. Epidemiology and extracutaneous comorbidities of severe acne in adolescence: a U.S. population-based study. Br J Dermatol. 2014 May;170(5):1136-42. Disclosure of Interest: None declared